2007
DOI: 10.1186/1471-2202-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium-derived factor protects retinal ganglion cells

Abstract: BackgroundRetinal ganglion cells (RGCs) are responsible for the transmission of visual signals to the brain. Progressive death of RGCs occurs in glaucoma and several other retinal diseases, which can lead to visual impairment and blindness. Pigment epithelium-derived factor (PEDF) is a potent antiangiogenic, neurotrophic and neuroprotective protein that can protect neurons from a variety of pathologic insults. We tested the effects of PEDF on the survival of cultured adult rat RGCs in the presence of glaucoma-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 48 publications
8
62
0
Order By: Relevance
“…Our RGC cultures isolated from neonatal rats were resistant to this excitotoxic insult, whereas adult RGCs appear to be more susceptible to excitotoxicity (Choi, 1985;Pang et al, 2007). Calcium is very important for early neuronal development such as axonal guidance and neuron maturation and this could explain such differences in these findings.…”
Section: Discussionmentioning
confidence: 70%
“…Our RGC cultures isolated from neonatal rats were resistant to this excitotoxic insult, whereas adult RGCs appear to be more susceptible to excitotoxicity (Choi, 1985;Pang et al, 2007). Calcium is very important for early neuronal development such as axonal guidance and neuron maturation and this could explain such differences in these findings.…”
Section: Discussionmentioning
confidence: 70%
“…[27][28][29][30][31][32] We found that polarized hES-RPE cells expressed much higher levels of PEDF in vitro than nonpolarized hES-RPE cells when evaluated by RT-PCR and Western blot analysis. To further quantify the PEDF secretion among the polarized hES-RPE, polarized fRPE cells and nonpolarized RPE counterparts, we used quantitative ELISA to measure the PEDF level in culture media from different RPE cells normalized to total protein of the cell lysates.…”
Section: Polarized Hes-rpe Cells Secreted High Level Of Pedfmentioning
confidence: 95%
“…Previous studies have shown that single growth factors, including basic fibroblast growth factor (FGF2), ciliary neurotrophic factor (CNTF), brain-derived neurotrophic factor (BDNF), glial-derived neurotrophic factor, pigment epitheliumderived factor (PEDF), and vascular endothelial growth factor-A (VEGFA), were able to enhance RGC survival and/or axon regeneration only in a transient and limited manner in vivo and/or in vitro. [23][24][25][26][27][28][29][30][31] Combinations of growth factors that support both soma survival and axonal regeneration have often generated improved results. BDNF and CNTF together, for example, induced increased axon regeneration, 32 while other studies showed that supplementing growth factors with additional factors such as forskolin or insulin further improved axon regeneration.…”
mentioning
confidence: 99%